2021
DOI: 10.1002/ett.4291
|View full text |Cite
|
Sign up to set email alerts
|

Signal to interference plus noise ratio improvement of a multi‐cell indoor visible light communication system through optimal parameter selection complying lighting constraints

Abstract: To achieve improved communication and illumination performances of a multi‐cell indoor visible light communication system, the selection of transmitter configuration and receiver's field of view (FoV) play a critical role. Based on multiple criteria decision modeling, a design‐centric methodology is proposed in this paper to determine the optimal transmitter configuration and receiver's FoV under lighting constraints. These optimal parameter selections are instrumental to obtain a highly uncorrelated channel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The proposed system achieves transmitter and receiver diversity by using repetition coding and equal gain combiner. A methodology based on optimal transmitter configuration using lighting constraints is proposed to improve the signal to interference plus noise ratio [26]. The optimal parameters selection at the transmitter are used to obtain an uncorrelated channel, mitigating co-channel interference from neighboring nodes and inter-symbol interference due to multipath reflection.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed system achieves transmitter and receiver diversity by using repetition coding and equal gain combiner. A methodology based on optimal transmitter configuration using lighting constraints is proposed to improve the signal to interference plus noise ratio [26]. The optimal parameters selection at the transmitter are used to obtain an uncorrelated channel, mitigating co-channel interference from neighboring nodes and inter-symbol interference due to multipath reflection.…”
Section: Related Workmentioning
confidence: 99%
“…4 To reduce the effect of the interference in the multiuser VLC systems, many works were assumed. The work in, 5 reduced the effect of the interference by manipulating the FOV of the receiver and the Tx with taking into account the lighting constrains. The results showed that reducing the FOV of the Tx and the receiver leads to enhance the signal to interference plus noise ratio (SINR) while using simple photodetector (PD).…”
Section: Introductionmentioning
confidence: 99%